(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
Correction: On 29th April 2015 the last line of the abstract was changed from the shelf life of Thai-Pangas in ice stored condition is 18 days for filleted and 21 days for the whole fish. TO the shelf life of Thai-Pangas in ice stored condition is 21 days and 18 days for the whole fish and fillets, respectively. The page numbers of this article were also changed from 175-181 to 177-183.. A comparative study on the shelf life of whole fish and fillet of cultured striped catfish (Pangasianodon hypophthalmus ) under ice storage condition was carried out by determining organoleptic and biochemical aspects in the month of September and October. It was found that shelf life of whole fish was 21 days where as fillet had slightly lower of 18 days shelf life. Value of pH changed from 7.07 to 6.97 after 24 days for whole fish and 6.88 for fillet after 21 days at the termination of experiment, pH remained to 6.5 for fillet after 18 days of ice storage. TVB-N value increased from an initial value of 1.68 mg/100g to 28.83 mg/100g in 21 days in whole fish and finally to rejection value of 35.89 mg/100g at the end of 24 days storage period. As for fillets TVB-N value was at acceptable level of 24.79 mg/100g until 18 days of storage at same condition. Myofibriller protein solubility gradually decreased with storage period for both whole fish and fillets. The results of this study indicated that in regard to organoleptic and biochemical aspects the shelf life of Thai-Pangas in ice stored condition is 18 days for filleted and 21 days for the whole fish. Res. Agric., Livest. Fish.2(1): 177-183, April 2015